Research on Labor Rights Protection Challenges and Countermeasures for Employees in Dujiangyan's Emerging Service Industries Amid the Digital Economy - Chu, Jialu (Asia Pacific Economic and Management Review, 2025)
Amidst the digital economy wave, Dujiangyan's 38,000 platform workers face five major fractures: labor relationship recognition, algorithmic overtime, fragmented social security, and more. This paper proposes a four-dimensional county-level solution integrating "legislation + technology + services + co-governance." Through closed-loop governance encompassing guidance, accounts, social security packages, service circles, collaborative mechanisms, and growth plans, it offers a replicable and scalable "Dujiangyan Model" for similar tourism destinations nationwide.